Research studies on patients' illness experience using the Narrative Medicine approach: a systematic review - Chiara Fioretti; Gabriella Pravettoni; Silvia Riva; Ketti Mazzocco; Serena Oliveri; Marianna Masiero (BMJ Open)
Objective Since its birth about 30 years ago, Narrative Medicine approach has increased in popularity in the medical context as well as in other disciplines. This paper aims to review Narrative Medicine research studies on patients' and their caregivers' illness experience.Setting and participants MEDLINE, Psycinfo, EBSCO Psychological and Behavioural Science, The Cochrane Library and CINAHL databases were searched to identify all the research studies which focused on the Narrative Medicine approach reported in the title, in the abstract and in the keywords the words ‘Narrative Medicine’ or ‘Narrative-based Medicine’. Primary and secondary outcome measures: number of participants, type of disease, race and age of participants, type of study, dependent variables, intervention methods, assessment.Results Of the 325 titles screened, we identified 10 research articles fitting the inclusion criteria. Our systematic review showed that research on Narrative Medicine has no common specific methodology: narrative in Medicine is used as an intervention protocol as well as an assessment tool. Patients' characteristics, types of disease and data analysis procedures differ among the screened studies.Conclusions Narrative Medicine research in medical practice needs to find clear and specific protocols to deepen the impact of narrative on medical practice and on patients' lives.